Comparison between ranitidine and ranitidine plus Caved-S in the treatment of gastric ulceration. Issue 12 (December 1985) - Morgan, A G; Pacsoo, C; McAdam, W A
Abstract : In a double blind endoscopically controlled study, 100 patients with gastric ulcers were treated with either ranitidine or ranitidine plus Caved-S. On single therapy, 58% of ulcers were healed at four weeks, 92% at eight weeks and 96% at 12 weeks. Combination therapy did not alter the healing rate, nor improve on the control of dyspeptic symptoms. No difference in healing rate was found between good and poor drug compliance patients. This suggests that ranitidine may be equally effective at lower dosages. Thirty seven patients had developed their ulcer while taking non-steroidal anti-inflammatory drugs. These patients were mainly elderly women who had a higher risk of bleeding (p = 0.006) from a large ulcer (p = 0.009).